Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Square Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VII SMP Negeri 20 Padang Tahun Pelajaran 2018/2019 - SHERLY FATIKA AULIA (Departemen Matematika, 2019)
MathermaticalWcommunication ability is importantaaspect of learningAmathematics. However, in factistudent’s mathematical communication ability in grade VII SMP Negeri 20 Padang was still low. Observationyshowed that student’s were less interest in mathematics learning wich was difficult and boring. One efforts that can be done-was applying cooperative learning model Think Pair Square type. Type of research was quasi experimentalpresearch with Randomized Control-Grup Only Design. Sampling wasudone by simple random sampling technique, Instrument waswfinal test student’s mathematical communication ability. Dataoanalysis used t test. Based on data analysis, it can be concluded that student’s mathematical communication ability whonlearning by cooperative learning model think pair square type isabetter than directdinstruction. Keywords—Cooperative learning-model, type think pairpsquare, student’szability of mathematics communication.